Suffering and martyrdom in the New Testament: studies presented to G.M. Styler by the Cambridge New Testament Seminar - Horbury, William; McNeil, Brian; Styler, G. (Cambridge University Press, 1981)
This is a collection of studies of suffering and martyrdom concentrating on the link, historically envisaged in different ways, between the sufferings of the faithful and the figure of Christ (or the messianic hope, in relation to one Jewish writer). The distinguished scholars contributing to this cohesive but many-sided book are C. F. D. Moule, J. C. O'Neill, B. E. Beck, B. Lindars, M. D. Hooker, W. F. Flemington, E. Bammel, J. P. M. Sweet, B. McNeil, W. Horbury, N. L. A. Lash and the late G. W. H. Lampe. All have been associated closely with the Cambridge New Testament Seminar and Professor Moule prefaces the volume with an account of the history of the Seminar and of its secretary for many years, G. M. Styler, in whose honour the collection is published. The importance and centrality of the topic will make the book of interest beyond the immediate circle of students of the New Testament, to those interested in patristic and Jewish studies and systematic theology.